Diastereoselective Synthesis of N-Alkylated Octahydroacridines via a Catalyst-Free SNAr Approach - Muddala, Nagendra Prasad; Nammalwar, Baskar; Selvaraju, Subhashini; Bunce, Richard A. (Synthesis, 2015)
A three-step diastereoselective synthesis of N-alkylated octahydroacridines has been developed from inexpensive starting materials. Alkylation of cyclohexanone with 2-fluorobenzyl bromide, followed by nitration para to the aromatic fluoro substituent provided the cyclization substrate in 61% yield. Finally, a tandem reductive amination-SNAr cyclization with NaCNBH3 furnished the target compounds in 74–92% yields. X-ray and 1H NMR studies permitted assignment of the stereochemistry of the B–C ring junction. The 3:1–10:1 preference for the cis-isomer was rationalized in terms of steric interactions in the imine reduction and a chair-like conformation for the cyclization. Hydride would be delivered to the molecular face opposite the fluoronitrobenzyl substituent at C-2 of the cyclohexanimine intermediate and the resulting amine would be positioned for addition to the SNAr acceptor ring via a chair-like conformation.
Keywords: octahydroacridines; tandem reductive amination-SNAr reactions; diastereoselective synthesis; steric control; chair-like conformation for ring closure